Effect of 3 Single‐Dose Regimens of Opicapone on Levodopa Pharmacokinetics, Catechol‐O‐Methyltransferase Activity and Motor Response in Patients With Parkinson Disease. Issue 3 (20th October 2015) - Rocha, José‐Francisco; Ferreira, Joaquim J.; Falcão, Amílcar; Santos, Ana; Pinto, Roberto; Nunes, Teresa; Almeida, Luis; Soares‐da‐Silva, Patrício
Abstract: This study determined the effects of single doses of opicapone (OPC), a novel third‐generation catechol‐ O ‐methyltransferase (COMT) inhibitor, on levodopa and 3‐ O ‐methyl‐levodopa (3‐OMD) pharmacokinetics (PK), COMT activity and motor fluctuations in patients with Parkinson disease (PD). Subjects received, in a double‐blind manner, 25, 50, and 100 mg OPC or placebo (PLC) in 4 separate treatment periods. The washout period between doses was at least 10 days. During each period, the OPC/PLC capsules were to be coadministered with the morning dose of 100/25 mg levodopa/carbidopa (LC) or levodopa/benserazide (LB) on day 3. In relation to PLC, levodopa exposure increased 3.7%, 16.4%, and 34.8% following 25, 50, or 100 mg OPC, respectively. Maximum S‐COMT inhibition (Emax ) ranged from 67.8% (25 mg OPC) to 100% (100 mg OPC). Peak and extent of S‐COMT inhibition were dose‐dependent. Maximum decrease in the plasma 3‐OMD was observed following administration of 100 mg OPC. Opicapone administered concomitantly with standard‐release 100/25 mg LC or LB improved motor performance. Treatments were generally well tolerated and safe. It was concluded that OPC is a new COMT inhibitor that significantly decreased COMT activity and increased systemic exposure to levodopa in PD patients with motor fluctuations.